STUDI TENTANG PERSEPSI DAN SIKAP MAHASISWA TERHADAP PROGRAM GERAKAN PAKAIAN RAPI DAN SOPAN DI FKIP UNIVERSITAS RIAU - EDDISON, AHMAD (Pelita Bangsa Pelestari Pancasila, 2016)
This research is being done with regards to the dressing habits of students from Teacher Training and Science Education Faculty, University of Riau. Therefore, the above contributed to the author to explore and research this study entitled “The Study of Students’ Perceptions and Attitudes towards Decent and Presentable Dressing in Teacher Training and Science Education Faculty, University of Riau.” The formulation of the program in this study is how perceptions and attitudes of students from Teacher Training and Science Education Faculty, University of Riau towards the program of decent and presentable dressing. The purpose of this research was to determine the perceptions and attitudes of students toward the program of “Decent and Presentable Dressing”, Teacher Training and Science Education Faculty” also known as FKIP in University of Riau.This research was done in the premises of Teacher Training and Science Education Faculty, University of Riau. The population within this research was recorded as 779 people. The sampling method used in this research is known as descriptive qualitative method and was guided by the opinions of Suharsimi Arikunto, this research utilized only 10% out of a total of 779 people, resulting only in the figure of 78 people. The instrument used in this research consisted of a questionnaire running up to a total of 20 questions and an interview of 5 questions. The data collected was then analyzed using descriptive qualitative through percentages calculation. From the total percentage calculation of the total respondents, 59.65% (range scale between 50.01% - 75.00%) agreed to the idea of decent and presentable dressing in the vicinity of University of Riau. Thus, the hypothesis of this research toward Decent and Presentable Dressing in Teacher Training and Science Education Faculty, University of Riau is accepted and represented by 13 questions supporting a total of 20 questions in the questionnaire.